Magnetic Polypyrrole-Gelatin-Barium Ferrite Cryogel as an Adsorbent for Chromium (VI) Removal - Milakin, Konstantin A; Taboubi, Oumayma; Hromádková, Jiřina; Bober, Patrycja (Gels (Basel, Switzerland), 2023)
Polypyrrole-gelatin aerogels, containing magnetic barium ferrite (BaFe) particles, (PPy-G-BaFe) were synthesized by oxidative cryopolymerization and used as adsorbents for the removal of Cr(VI) from aqueous media. The removal was performed at pH 4, which was shown to be the optimal value, due to HCrO4- being the dominant species in these conditions and its more favorable adsorption and reduction compared to CrO42-, present at pH > 4. It was found that the presence of magnetic BaFe particles had no effect on the adsorption performance of PPy aerogels in terms of capacity and kinetics, which was attributed to its relatively low content in the composite. After the adsorption, the presence of chromium in the composites was confirmed by EDX and its electrostatic interaction with the adsorbent was pointed at by vibrational spectroscopy, corresponding to the accepted adsorption mechanism. The adsorption kinetics followed the pseudo-second-order model pointing at chemisorption being the rate-limiting step. The adsorption isotherm data was best fitting with the Temkin model. The maximum adsorption capacity, calculated using the Langmuir model, was 255.8 mg g-1 (the maximum experimental value was 161.6 mg g-1). Additionally, the possibility of Cr(VI) adsorption in the presence of Cl-, Br-, NO3- and SO42- as interfering ions was shown.
Keywords: polypyrrole; chromium; cryogel; adsorption; water purification